Marginal Returns to Public Universities - Mountjoy, Jack (Quarterly Journal of Economics, 2026)
This article studies the returns to enrolling in U.S. public universities by comparing the long-term outcomes of barely admitted versus barely rejected applicants. I use administrative admission records spanning all 35 public universities in Texas, which collectively enroll 10% of all American public university students, to systematically identify and employ decentralized cutoffs in SAT/ACT scores that generate discontinuities in admission and enrollment. The typical marginally admitted student gains an additional year of education in the four-year sector, becomes 12 percentage points more likely to ever earn a bachelor’s degree, and eventually earns 8% more than their marginally rejected but otherwise identical counterpart. Marginally admitted students pay no additional tuition costs thanks to offsetting grant aid; cost-benefit calculations show internal rates of return of 26% for the marginal students themselves, 16% for society (which must pay for the additional education), and 7% for the government budget. Earnings gains are similar across admitting institutions of varying selectivity, but smaller for students from low-income families, who spend more time enrolled but complete fewer degrees and major in less lucrative fields. Finally, I develop a method to separately identify effects for students on the extensive margin of attending any university versus those on the margin of attending a more selective one, revealing larger effects on the extensive margin.